ANALISIS HALAL SUPPLY CHAIN MANAGEMENT PADA PRODUK FROZEN FOOD SOSIS (STUDI KASUS DI PAWONE BU WUNI PONOROGO): Analysis Of Halal Supply Chain ​​Management On Frozen Food Sausage Products (Case Study In Pawone Bu Wuni Ponorogo) - Devi Urianty Miftahul Rohmah; Muhammad Nur Kholis; Abdillah Hafidz (Universitas Darussalam Gontor, 2022)
The average growth of the food and beverage market in 2013-2017 is predicted to be above 10%, while frozen food products they are predicted to grow to 16.6%. The purpose of this study was to analyze the activities of each stakeholder related to Pawone Bu Wuni using the SCOR method and the halal supply chain of sausage products in Pawone Bu Wuni. The sausage,raw material used is a raw material that is classified as a material that has a fairly high risk because it uses chicken meat as its basic ingredient and has a fairly high selling value. The raw material for chicken meat used is obtained from the RPA (chicken slaughterhouse) which needs to be reviewed regarding the implementation of a halal assurance system for chicken slaughterhouses that uses 11 halal manual criteria that have been set by MUI. The SCOR method is used to analyze every stakeholder activity that is directly related to Mrs. Wuni, so that the flow pattern of the halal supply chain can be described through the SCOR method and the Halal Assurance System (SJH). Flow Pattern of Halal Supply Chain Sausage Products supplier, manufacturer, retailer, RPA Siantrah stakeholder activities: plan, source, make, deliver, Pawone Bu Wuni plan, source, make, deliver, return, IKM Mart: plan, source, deliver, return. Halal supply chain analysis of RPA Siantrah Ponorogo's assessment with a